Analisis Pengaruh Fixed Asset Turnover (Fato) Dan Return On Asset (Roa) Terhadap Return Saham PT Krakatau Steel Tbk - Islam, Mia Nur; Rimawan, M.; Alwi (CV ODIS, 2024)
The aim of this research is to analyze the influence of Fixed Asset Turnover (Fato) and Return on Assets (ROA) on PT Krakatau Steel Tbk's share returns. The population in this study was 13 years and the sample used was 10 years. The data used is secondary data. The results of this research partially Fixed Asset Turnover (FATO) and Return on Assets (ROA) Tbk have no effect on PT Krakatau Steel Tbk Share Returns. Meanwhile, Simultaneous Fixed Asset Turnover (Fato) and Return on Assets (ROA) Tbk have no effect on PT Krakatau Steel Tbk Share Returns